Assessment of Mothers Knowledge and Practices with Hemophilic Children type A at Azadi Teaching Hospital in Kirkuk City - mohammed, Aram; hattab, Khatam (Iraqi National Journal of Nursing Specialties, 2013)
Objective: The study aims to assess the knowledge and practices of mothers with hemophilia children type - A - ,socio-economic status and association between mother demographic information with their knowledge and practicestoward their children in Azadi Teaching Hospital in Kirkuk.Methodology: Descriptive study no probability (purposive) sample. Selected Fifty-five of mothers having hemophiliachildren, started from November 2012 to May 2013. Study was carried out in the Azadi teaching hospital inKirkuk. By using questionnaire which consists from five parts include demographic characteristics for mother andchildren, socio-economic, Knowledge and practices data gathered, by direct interview with the mothers in thehospital. Reliability and content validity of questioner were identified form of the pilot study. Descriptive and inferentialstatistical used to analysis of data.Results: The results of the study (30.9%) of the mothers were aged (40 - 44) and (43.6%) were graduates from primaryschool. And their hemophilia children in all sample sex male, (41.8%) of hemophilia children were aged between(5-9) years though (30.9 %) are not in school and that (69.1%) of the families have one child hemophilia infectedand (27.6%) were diagnosis bleeding in joint , level of severity of the disease (65.5%) was moderate,(98.2%) of family depended on hospital to provide factor eight and other treatment to hemophilia child whenbleeding. socio – economic status of family show ( 61.8%) low status. (83.6%) of mothers uncertain of their informationabout hemophilia, mother practices were (72.7%) sometimes and (23.6%) never done good practice totheir hemophilia children.Recommendations: Develop special booklet for mothers local languages (Kurdish , Turkish ) develop programs andawareness courses (theoretical and practical) for mothers and support family financial improve and provide factoreighth for hospitals and health center where patients found.